Financializing Desalination: Rethinking the Returns of Big Infrastructure. (13th June 2016) - Loftus, Alex; March, Hug
Abstract: Against the trend prevalent during the 1990s and 2000s, large‐scale infrastructural projects have made a comeback in the water sector. Although sometimes framed as part of a broader sustainable transition, the return of big infrastructure is a much more complicated story in which finance has played a crucial role. In the following article, we explore this encounter between finance and water infrastructure using the case of Britain's first experiment in desalination technologies, the Thames Water Desalination Plant (TWDP). On the surface, the plant appears to be a classic example of the successes of normative industrial ecology, in which sustainability challenges have been met with forward‐thinking green innovations. However, the TWDP is utterly dependent on a byzantine financial model, which has shaped Thames Water's investment strategy over the last decade. This article returns to the fundamental question of whether London ever needed a desalination plant in the first place. Deploying an urban political ecology approach, we demonstrate how the plant is simultaneously an iconic illustration of ecological modernization and a fragile example of an infrastructure‐heavy solution to the demands of financialization. Understanding the development of the TWDP requires a focus on the scalar interactions between flows of finance, waste, energy and water that are woven through the hydrosocial cycle of London.